2014
DOI: 10.12659/msm.890756
|View full text |Cite
|
Sign up to set email alerts
|

Toxic Effects of Chronic Mercury Exposure on the Retinal Nerve Fiber Layer and Macular and Choroidal Thickness in Industrial Mercury Battery Workers

Abstract: BackgroundThe aim of this study was to evaluate the toxic effects of mercury on retinal nerve fiber layer thickness (RNFLT), macular thickness (MT), and choroidal thickness (CT) by using spectral-domain optical coherence tomography (SD-OCT) in battery industry workers who had been chronically exposed to mercury.Material/MethodsBattery factory workers (n=31) and healthy non-factory employee controls (n=15) participated in the study. Participants were divided into 3 groups: Group 1 (n=15) was factory workers who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 39 publications
0
13
1
Order By: Relevance
“…Mercury is taken up by the retina of mercury-exposed mice [ 34 , 35 ], rats [ 36 ], and monkeys [ 17 , 36 , 37 ]. Exposure to mercury affects human vision [ 32 , 38 , 39 ], and people with higher blood levels of mercury from amalgam fillings have more retinal thinning on optical coherence tomography than controls [ 40 ]. Mercury damages human RPE cells in culture [ 41 ], and inorganic mercury is taken up in RPE cells via amino acid transporters [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mercury is taken up by the retina of mercury-exposed mice [ 34 , 35 ], rats [ 36 ], and monkeys [ 17 , 36 , 37 ]. Exposure to mercury affects human vision [ 32 , 38 , 39 ], and people with higher blood levels of mercury from amalgam fillings have more retinal thinning on optical coherence tomography than controls [ 40 ]. Mercury damages human RPE cells in culture [ 41 ], and inorganic mercury is taken up in RPE cells via amino acid transporters [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Once the lungs have absorbed the inhaled vapor, the mercury can reach different tissues via the bloodstream, with the primary target the CNS and eyes because of proximity [2,23]. When it is oxidized, it cannot penetrate the bloodbarrier again and remains for prolonged periods in tissues [2,7,8,23].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of electrophysiology tests and current clinical examination techniques such as auto uorescence or optical coherence tomography (OCT) have suggested that besides central nervous system (CNS) poisoning, which is widely accepted, the retina also is involved and that not all visual functional alterations are caused by high visual pathway damage [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toxic metals such as mercury have been implicated in neurological disorders, and could act in combination with genetic or other susceptibilities to cause widespread cell damage [5,6]. In addition, mercury has been thought to be responsible for several human retinal disorders [7,8,9]. Mercury has been located in the adult primate retina and optic nerve after exposure to mercury vapor [10].…”
Section: Introductionmentioning
confidence: 99%